2021
DOI: 10.1093/ecco-jcc/jjab076.389
|View full text |Cite
|
Sign up to set email alerts
|

P263 Influence of Crohn′s Disease phenotype in the retention rate of ustekinumab treatment: SUSTAIN Study

Abstract: Background Crohn′s disease (CD) is a progressive inflammatory bowel disease that can lead to complications such as strictures or penetrating disease, and ultimately surgery, representing a complex clinical challenge in the care of patients. We aimed to evaluate the influence of CD phenotype in the retention rate of ustekinumab in the Sustain study. Methods Retrospective, multicentre study (>60 sites) including patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…34 Other studies found no difference in ustekinumab response between different disease behaviours. [35][36][37][38] With regard to disease location, our study also showed that CD patients with ileo-colonic disease were more likely to achieve biological remission than patients with ileal disease. Several studies have shown that patients with colonic CD had lower CRP levels and improved response rates to ustekinumab therapy compared to CD patients with other disease locations.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…34 Other studies found no difference in ustekinumab response between different disease behaviours. [35][36][37][38] With regard to disease location, our study also showed that CD patients with ileo-colonic disease were more likely to achieve biological remission than patients with ileal disease. Several studies have shown that patients with colonic CD had lower CRP levels and improved response rates to ustekinumab therapy compared to CD patients with other disease locations.…”
Section: Discussionsupporting
confidence: 56%
“… 34 Other studies found no difference in ustekinumab response between different disease behaviours. 35 38 …”
Section: Discussionmentioning
confidence: 99%